STRATEGI PEMBANGUNAN PERTANIAN DALAM ERA GLOBALISASI - Purbayu Budi Santoso (Jurnal Dinamika Ekonomi & Bisnis, 2004)
Industrialization strategy took by Indonesia, based on high technology and capital intensive had been look as a wrong strategy. It is not appropriate for Indonesia because Indonesian economy is based on the agricultural sector, so industrialization strategy based on high technology and capital intensive created several kinds of inefficiency and resources misallocation. This strategy had created weak structure of Indonesian economy, by which industry sector does not have strong linkages with other sectors, especially agricultural sector.It should be noted, that later on, industrialization strategy in Indonesia must be based on agricultural sector. The objective of this paper is to explain the strategy of agricultural development in Indonesia. Human resources development in agricultural sector is a key factor in developing agricultural sector. Financial support is look as one of another important strategy also.